Cancellation of elective surgeries in a Brazilian public hospital: reasons and estimated reduction - Alves Corral dos Santos, Gisele Aparecida [UNESP]; Mangini Bocchi, Silvia Cristina [UNESP] (Assoc Brasileira Enfermagem, 2017)
Objective: To characterize cancellations of elective surgeries according to clinical and non-clinical reasons, as well as to verify seasonal influence and determine the estimated reduction of the index. Method: Quantitative, descriptive and retrospective study with secondary data extracted from the Public Hospital of the State of Sao Paulo database. Results: Out of the 8,443 (100%) elective surgeries scheduled, 7,870 (93.21%) were performed and 573 (6.79%) were canceled. Out of these 573 (100%) people, 48.33% were canceled for clinical reasons and 46.40% were for non-clinical reasons. Among the non-clinical reasons for surgery cancellations, those related to medical reasons stood out: at the request of the surgeon/change of approach (17.93%), followed by non-hospitalized patient (8.96%). There was no indication of seasonality regarding the reasons for cancellation in the assessed period. Conclusion: Although the rate of elective surgeries cancellations is lower than that of other hospitals with similar characteristics, it is still possible to reduce it from 6.79% to 1.36%, considering that 80% of the reasons for cancellation are avoidable.
Keywords: Elective Surgical Procedures; Hospital Surgical Center; Hospital Administration; Public Hospitals; Health Assessment